Asymmetric Substrate Integrated Waveguide Leaky Wave Antenna with Open Stop Band Suppression and Radiation Efficiency Equalization through Broadside - Agrawal, Rahul; Belwal, Pravesh; Gupta, Suresh (Společnost pro radioelektronické inženýrství, 2018)
A planar asymmetric substrate integrated wave¬guide leaky wave antenna is proposed with open stop band suppression and radiation efficiency equalization through broadside for the Ku-band. The stop-band behavior exhib¬ited at broadside in the 1-D periodic structure is signifi¬cantly reduced using reflection cancellation technique by placing the two slots at a quarter distance within the unit cell. Furthermore, asymmetric technique is applied. The asymmetry is introduced with respect to both axial and transversal axis of the structure so as to match the at-broadside Bloch impedance and off-broadside Bloch im¬pedance. This provides total open stop band suppression and radiation efficiency improvement as well as equaliza-tion through broadside. The problem is analyzed with the help of Bloch impedance behavior. For illustration of the above techniques; single slot, double slot and asymmetric designs are developed for the proposed leaky wave an¬tenna. The final asymmetric design after optimization is fabricated. Measured results are almost consistent with the simulation results with complete suppression of open stop band, efficiency improvement and equalization through broadside providing continuous beam scanning from –32° to +27° with constant gain of ~12.5 dBi.
Keywords: Leaky wave antenna; substrate integrated waveguide; open stop band; reflection cancellation; asymmetry; efficiency equalization; broadside